Mandatory Minimums and the Sentencing of Federal Drug Crimes - David J. Bjerk (Institute of Labor Economics (IZA), 2017)
The United States federal mandatory minimums have been controversial not only because of the length of the mandatory sentences for even first-time offenders, but also because the eligibility quantities for crack are very small when compared to those for other drugs. This paper shows that the actual impact of these mandatory minimums on sentencing is quite nuanced. A large fraction of mandatory minimum eligible offenders, particularly first-time offenders, are able to avoid these mandatory minimums. Moreover, despite lower quantity eligibility thresholds for crack, a smaller fraction of crack offenders are eligible for mandatory minimums relative to other drugs. Furthermore, while being just eligible for a mandatory minimum increases sentence length on average, the impact is not uniform across drugs. Notably, sentences for crack offenders are generally sufficiently long such that, on average, sentences for crack offenders are not impacted by eligibility for a mandatory minimum. In summary, the discrepancy in federal sentencing between crack offenders and those convicted for other drugs does not appear to be driven by mandatory minimums, but rather other aspects of federal sentencing policy and norms.
Keywords: J15; K14; K40; 330; mandatory minimum sentencing; crack cocaine; sentencing guidelines